Іn relation to the question of improvement of investment climate of Ukraine - Івашко, Олена Анатоліївна; Ivashko, Olena (Publishing Center of The internatioanal scientific association of economists "Consilium", 2014)
The article is dedicated to the determination of problems which hinder forming of favorable investment climate of Ukraine. Certainly priorities of investment policy of the state are in the conditions of the crisis phenomena in an economy. Grounded necessity of proceeding in activity of the dedicated modes of investing for Ukraine. Стаття присвячена визначенню проблем, які перешкоджають формуванню сприятливого інвестиційного клімату України. Визначено пріоритети інвестиційної політики держави в умовах кризових явищ в економіці. Обґрунтовано необхідність відновлення діяльності спеціальних режимів інвестування в Україні.
Щодо питання покращення інвестиційного клімату України
Keywords: інвестиції; інвестиційний клімат; спеціальні режими інвестиційної діяльності; вільні економічні зони; території пріоритетного розвитку; investments; investment climate; special investment regimes; free economic zones; territories of priority development